FPGA USAGE FOR PROCESSING IMAGE OF LASER BEAM (Transport systems and technologies, 2021)
Considered modern problems of laser image processing. An analysis of existing solutions and recent research in the field of image processing of laser beam. Determined that the latter solutions have a number of disadvantages in terms of increasing the speed and density of information flow. There are also problems with excessive power consumption during image processing due to excess power.Also presented method of processing image of laser beam with the use of FPGA and parallelhierarchical transformation. Performing simulation modeling of methods for processing the coordinates of laser beam spots and its results are presented.Presented comparison of the results of image processing using a personal computer and using FPGA.The obtained results allow to evaluate the efficiency of FPGA application and methods with the use of parallel-hierarchical transformation during image processing of laser beams.Due to low power consumption and efficient image processing using FPGA and parallelhierarchical transformation - this technology has great prospects for use in the automotive industry. It can be used to improve the development of unmanned vehicle control, especially for electric vehicles.
Keywords: parallel-hierarchical transformations, FPGA, image processing, laser beams, laser spots.